2023
DOI: 10.1007/s11356-023-29061-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of meteorological parameters and air pollutants on airborne concentration of Betula pollen and Bet v 1 allergen

Jana Ščevková,
Jozef Dušička,
Eva Zahradníková
et al.

Abstract: The intensity of birch pollen season is expressed by seasonal pollen integral (SPIn, the sum of the mean daily pollen concentration during the birch pollination period) and the amount of Bet v 1 allergen released per birch pollen grain expressed by pollen allergen potency (PAP). Betula pollen and Bet v 1 allergen were simultaneously measured in the air of Bratislava from 2019 to 2022 by using two Burkard traps (Hirst-type and cyclone) in order to evaluate the causes of the seasonal variation in the SPIn and PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…During the course of our study, the intensity of tree pollen seasons, expressed as SPIn, peak value and HD, increased at both localities, although all three characteristics were significant only for oak. Our results agree with the conclusions of Adams-Groom et al ( 2022 ) and Ščevková et al ( 2023 ) that warmer and humid weather in the latter half of the year before pollination stimulates pollen production in woody plants, increasing the intensity of their pollen season.…”
Section: Discussionsupporting
confidence: 93%
“…During the course of our study, the intensity of tree pollen seasons, expressed as SPIn, peak value and HD, increased at both localities, although all three characteristics were significant only for oak. Our results agree with the conclusions of Adams-Groom et al ( 2022 ) and Ščevková et al ( 2023 ) that warmer and humid weather in the latter half of the year before pollination stimulates pollen production in woody plants, increasing the intensity of their pollen season.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, as shown in the literature, the urban heat island (UHI) effect may affect levels of chemical air pollutants and be responsible for an increase in allergen content and production. Furthermore, pollen species may be different in urban and rural environments [120,148]. Although there are still few studies regarding occupational allergies in relation to air pollutants, they may have a negative and significant impact on worker's health and quality of life in different categories of workers in many sectors (i.e., construction, agriculture, farming, health care), resulting in economic losses and a high prevalence of allergic respiratory diseases [145,147].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that people of many countries living in urban areas are more sensitive to respiratory allergies, and as a consequence, the prevalence of pollinosis is increasing, especially in polluted cities [120][121][122]. Pollen taxa may differ in urban and rural environments [12].…”
Section: Air Pollutants Pollen and Public Healthmentioning
confidence: 99%
“…Studies have also identified associations between seasonal variations in pollen counts and environmental conditions, with factors like air pollutants influencing pollen allergen potency. High levels of air pollutants, particularly during early spring and the pollen season, have been linked to elevated Betula pollen allergen potency ( 53 ).…”
Section: Pollution Pollen Production and Atmospheric Co 2 ...mentioning
confidence: 99%
“…Furthermore, the interaction between atmospheric pollution (PM, NO 2 , SO 2 , and O 3 ) and pollen exposure during pollen seasons exacerbates respiratory symptoms in allergic individuals ( 47 , 50 , 52 , 53 ). Specifically, uncontrolled rhinitis symptoms have shown a 25% increase for every interquartile range rise in ozone levels during the grass pollen season ( 51 ).…”
Section: Pollution Pollen Production and Atmospheric Co 2 ...mentioning
confidence: 99%

Air pollution and rhinitis

Rosario,
Urrutia-Pereira,
Murrieta-Aguttes
et al. 2024
Front. Allergy